Related Party Transaction Berpengaruh Terhadap Biaya Audit: Related Party Transaction Influences Audit Costs - Senato Erasandi (Journal of Accounting Science, 2020)
The purpose of this study is to analyze the effect of related party transactions on audit fees. This study uses 67 samples listed on the Indonesia Stock Exchange for the period 2017 to 2018. The analysis used in this study is the Multiple Regression analysis model that is processed with SPSS 20 software. This study found that related party transactions were positively and significantly related to audit fees. The results show that related party transactions can cause the company to have a high risk so that it can increase the audit fees paid by the company